2020
DOI: 10.4025/actascianimsci.v43i1.49033
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the level and the action period of fiber in diets to laying hens

Abstract: The aim of the present study was to evaluate the relationship between the level of fiber and its action period in diets to laying hens on performance and egg quality. 180 Hisex white hens (65 weeks-old) were randomly allocated to 3 groups of 60 birds each, comprising 10 replicates of six birds per treatment. The experimental design was factorial scheme considering three levels of fiber (2.50, 4.87 and 7.24%) in birds’ diets, and three action periods of this fiber (short - 21 days, medium - 56 days, and long - … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In this same process, higher fiber levels in the diets tend to hurt the performance of the hens. Rufino et al (2021) reported a lower effect of fiber on performance and egg quality in the short-term. However, the same authors pointed a great reduction in these results when hens fed diets with a high level of fiber for the medium or long-term.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…In this same process, higher fiber levels in the diets tend to hurt the performance of the hens. Rufino et al (2021) reported a lower effect of fiber on performance and egg quality in the short-term. However, the same authors pointed a great reduction in these results when hens fed diets with a high level of fiber for the medium or long-term.…”
Section: Resultsmentioning
confidence: 94%
“…Animal Sciences, v. 45, e57534, 2023 tend to change all gut functioning. And how the absorption of poultry diets nutrients directly depending on mechanisms of the gut mucosa, where the integrity of epithelial cells and the action of digestive enzymes in the lumen are essential for nutrients to be well used (Jiménez-Moreno, Frikha, Coca-Sinova, García & Mateos, 2013), the presence of blockages in these processes can cause significant losses on performance and blocking the nutrients to be deposited in the eggs (Rufino et al, 2021). According to Yokhana et al (2015), high levels of fiber normally cause disturbances in the energy metabolism of the hen, which are even more evident in young birds where the physiology is more sensitive and tends to present a rapid response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations